2021
DOI: 10.1016/j.str.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Atomic insights into ML-SI3 mediated human TRPML1 inhibition

Abstract: Highlights d A 2.9Å cryo-EM structure of ML-SI3-bound TRPML1 reveals a closed conformation d The TRPML1 inhibitor ML-SI3 binds the same cavity as its agonist ML-SA1 d ML-SI3 competes with ML-SA1 to block the channel activity d TRPML1 inactivation via ML-SI3 is independent of phosphoinositide regulation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…Whole-endolysosome ML1-mediated currents ( I ML1 ) were activated by ML-SAs ( Figures 1C – 1E ), which included ML-SA1 ( Shen et al, 2012 ) and the more potent ML-SA5 and ML-SA8 ( Sahoo et al, 2017 ; Yu et al, 2020 ) (potency SA1 < SA5 < SA8; Figure S1E ), and inhibited by ML-SI3 and ML-SI4 ( Sahoo et al, 2017 ; Yu et al, 2020 ) ( Figure S1F ). Note that the specificities of ML-SAs and ML-SIs have been previously validated using ML1 KOs ( Sahoo et al, 2017 ; Shen et al, 2012 ; Yu et al, 2020 ; Zhang et al, 2016 ) and confirmed in the atomic-resolution co-structures ( Schmiege et al, 2017 ; Schmiege et al, 2021 ). Remarkably, whole-endolysosome I ML1 was 30-to-75-fold larger in MeWo and M12 cells compared with normal melanocytes ( Figure 1F ).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Whole-endolysosome ML1-mediated currents ( I ML1 ) were activated by ML-SAs ( Figures 1C – 1E ), which included ML-SA1 ( Shen et al, 2012 ) and the more potent ML-SA5 and ML-SA8 ( Sahoo et al, 2017 ; Yu et al, 2020 ) (potency SA1 < SA5 < SA8; Figure S1E ), and inhibited by ML-SI3 and ML-SI4 ( Sahoo et al, 2017 ; Yu et al, 2020 ) ( Figure S1F ). Note that the specificities of ML-SAs and ML-SIs have been previously validated using ML1 KOs ( Sahoo et al, 2017 ; Shen et al, 2012 ; Yu et al, 2020 ; Zhang et al, 2016 ) and confirmed in the atomic-resolution co-structures ( Schmiege et al, 2017 ; Schmiege et al, 2021 ). Remarkably, whole-endolysosome I ML1 was 30-to-75-fold larger in MeWo and M12 cells compared with normal melanocytes ( Figure 1F ).…”
Section: Resultsmentioning
confidence: 57%
“…The related ML2 and ML3 channels are also permeable to Ca 2+ , as well as heavy metal ions, but are more restrictively expressed ( Cheng et al, 2010 ; Li et al, 2019 ). Using TRPML-specific synthetic agonists (ML-SAs) and synthetic inhibitors (ML-SIs), which bind directly to TRPML proteins in the atomic-resolution co-structures ( Schmiege et al, 2017 ; Schmiege et al, 2021 ), we and others have demonstrated that TRPML channels, especially ML1, play essential roles in various lysosomal functions, which include lysosome movement, membrane trafficking, lysosomal exocytosis, lysosome biogenesis, and heavy metal homeostasis ( Dong et al, 2008 ; Li et al, 2016 ; Minckley et al, 2019 ; Peng et al, 2020 ; Samie et al, 2013 ; Yu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of TRPML1, reactive oxygen species may serve such a role (Zhang et al., 2016), but whether they synergize with PI(3,5)P 2 remains to be established. Intriguingly, the TRPML1 blocker ML‐SI3 blocks channel activation by synthetic activators but not PI(3,5)P 2 (Schmiege et al., 2021). Yet it has functional effects on processes such as autophagy (Scotto Rosato et al., 2019; Wang et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The deep S4-S5 site in TRPC6 harbors the inhibitor BTDM ( Guo et al, 2022 ). The deep portal site binds the agonist ML-SA1 ( Schmiege et al, 2017 ; Zhou et al, 2017 ) and inhibitor ML-SI3 ( Schmiege et al, 2021 ) in TRPML1, inhibitors HC-070 ( Song et al, 2021 ) and Pico145 ( Wright et al, 2020 ) in TRPC5, and A-967079 ( Paulsen et al, 2015 ) in TRPA1. Many ligands have been found to bind to the S1-S4 base site, including Ca 2+ that plays a role of an activator in TRPC3, TRPM2, and TRPM4 and an inhibitor in TRPM5 ( Autzen et al, 2018 ; Huang et al, 2018 ; Wang et al, 2018 ; Zhang et al, 2018 ; Ruan et al, 2021 ; Guo et al, 2022 ), Na + in TRPC4 ( Duan et al, 2018 ), a cation in TRPC5 ( Duan et al, 2019 ), the inhibitors clemizole in TRPC5 ( Song et al, 2021 ), and SAR7334 ( Guo et al, 2022 ) and AM-1473 ( Bai et al, 2020 ) in TRPC6 as well as the agonists WS-12 and icilin ( Yin et al, 2019 ) and inhibitors TC-I 2014 and AMTB ( Diver et al, 2019 ) in TRPM8.…”
Section: Introductionmentioning
confidence: 99%